PEMODELAN DINAMIKA FLUIDA PADA FUEL INJECTOR MOTOR BENSIN 4 LANGKAH - Khambali, Khambali; Fadhilah, Intan; Hartono, Moh; Farida, Nike Nur (Otopro, 2025)
This study aims to model fluid dynamics in the fuel injector of a four-stroke gasoline engine, with a focus on the relationship between fluid pressure and flow rate. The size of the fuel droplet is a key factor that affects combustion efficiency. Droplet size can be controlled through the regulation of injection speed and pressure. In this study, data on injection speed and pressure were collected using an injector tester, injector plunger, and fuel pump tester pressure gauge. The data show that at a higher injection speed (80 m/s), the fuel droplet diameter decreases more rapidly, producing smaller droplets and enhancing combustion efficiency. A similar pattern was observed at higher injection pressures (50 bar), where the droplets atomized more quickly, allowing for a more homogeneous air-fuel mixture. The results illustrate that both higher injection speed and pressure support a more efficient atomization process, reduce emissions, and improve engine efficiency. This study concludes that proper regulation of injection speed and pressure is crucial to optimize engine performance and reduce exhaust emissions. The findings can be used to design more efficient fuel injection systems and provide recommendations for the development of future injection technologies